Generalized Net Model of the Foreign Object Principle and its Network Physiology Interpretations - Atanassov, Krassimir; Staneva, Galya; Pencheva, Tania (Frontiers in Network Physiology, 2022)
The foreign object principle has been introduced in a formalized form for first time. Proven as a suitable tool for modelling of parallel processes flowing in real time, the generalized nets have been used for an interpretation of the foreign object principle. It is illustrated by some examples from network physiology.